PERBEDAAN POLA SIDIK BIBIR METODE DOMIATY BERDASARKAN GENDER PADA MAHASISWA FAKULTAS KEDOKTERAN GIGI UNIVERSITAS BRAWIJAYA: - - Astika Swastirani; Eriko Prawestiningtyas; Farihah Septina; Riska Yanti (E-Prodenta Journal of Dentistry, 2023)
Background: Crime or criminal action is an act of harming someone. Criminal action is contrary to legal, social or religious norms. Based on the data from the Central Statistics Agency (CSA), generally, crime cases in Indonesia increased in the 2014-2016 period. Lip prints can be used for forensic identification to resolve criminal cases. Lip prints are a pattern of wrinkles and fissures on the surface of the lip mucosa. The pattern on the lip is different for each individual because it is influenced by factors of gender, race and age. Purpose: The purpose of this study is to determine the differences between lip prints pattern using Domiaty method on sexual dimorphism of students of Faculty of Dentistry Brawijaya University. Methods: The sample used is taken from 80 people. The subjects’ lip is applied by lipstick then sticked with sticky tape to get lip prints pattern, to be analyzed using Adobe Photoshop CC 2015 software, then classified with Domiaty type. Results: The data is analyzed by using Fisher exact test. The result obtained is a significance value of p <0.05. Conclusion: The conclusion from this study is there are differences in lip print patterns between men and women. The dominant lip print pattern found in men is type C, whereas the dominant pattern in women is type H.